Bangladeshi children with acute diarrhoea show faecal microbiomes with increased Streptococcus abundance, irrespective of diarrhoea aetiology. (7th August 2018) - Kieser, Silas; Sarker, Shafiqul A.; Sakwinska, Olga; Foata, Francis; Sultana, Shamima; Khan, Zeenat; Islam, Shoheb; Porta, Nadine; Combremont, Séverine; Betrisey, Bertrand; Fournier, Coralie; Charpagne, Aline; et al.
Summary: We report streptococcal dysbiosis in acute diarrhoea irrespective of aetiology. Compared with 20 healthy local controls, 71 Bangladeshi children hospitalized with acute diarrhoea (AD) of viral, mixed viral/bacterial, bacterial and unknown aetiology showed a significantly decreased bacterial diversity with loss of pathways characteristic for the healthy distal colon microbiome (mannan degradation, methylerythritol phosphate and thiamin biosynthesis), an increased proportion of faecal streptococci belonging to the Streptococcus bovis and Streptococcus salivarius species complexes, and an increased level of E. coli ‐associated virulence genes. No enteropathogens could be attributed to a subgroup of patients. Elevated lytic coliphage DNA was detected in 2 out of 5 investigated enteroaggregative E. coli (EAEC)‐infected patients. Streptococcal outgrowth in AD is discussed as a potential nutrient‐driven consequence of glucose provided with oral rehydration solution.